Climate change and poverty: vulnerability, impacts, and alleviation strategies. (2nd May 2014) - Leichenko, Robin; Silva, Julie A.
<x xml:space="preserve">Abstract</x> Poverty is widely understood to be a key factor that increases the propensity for individuals and households to be harmed by climatic shocks and stresses. This review explores recent literature at the nexus of climate change impacts, vulnerability, and poverty. Within this literature, poverty is increasingly recognized as a dynamic and multidimensional condition that is shaped by the interplay of social, economic, political, and environmental processes, individual and community characteristics, and historical circumstances. While climate change is never seen as a sole cause of poverty, research has identified numerous direct and indirect channels through which climatic variability and change may exacerbate poverty, particularly in less developed countries and regions. Recent studies have also investigated the effects of climate change on economic growth and poverty levels, formation of poverty traps, and poverty alleviation efforts. These studies demonstrate that climate change‐poverty linkages are complex, multifaceted, and context‐specific. Priority issues for future work include greater attention to factors that promote resilience of poor populations, a stronger focus on nonmonetary dimensions of poverty, investigation of the impacts of climate change on relative poverty and inequality, and exploration of the poverty impacts of extreme climate change. For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.